2022
DOI: 10.1002/ecy.3720
|View full text |Cite
|
Sign up to set email alerts
|

Priority effects alter the colonization success of a host‐associated parasite and mutualist

Abstract: Priority effects shape the assembly of free-living communities and host-associated communities. However, the current literature does not fully incorporate two features of host-symbiont interactions, correlated host responses to multiple symbionts and ontogenetic changes in host responses to symbionts, leading to an incomplete picture of the role of priority effects in host-associated communities.We factorially manipulated the inoculation timing of two plant symbionts (mutualistic rhizobia bacteria and parasiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…and Zn biofortification influence plant nodulation, as well as to the complex interactions among plants, microbes, and soil in biofortification processes [43]. As for the independent effect of both factors on nodulation, the inhibitory effect in the plants inoculated with T09 and T18 (both identified as T. gamsii) may be a result of the colonization dynamics in the rhizosphere, considering that nodulation success may be influenced by the timing and sequence in rhizosphere interactions between different microorganisms [59]. These results are consistent with a related study by Khan et al [60], where some Trichoderma strains enhanced plant growth and nutrient uptake by promoting root development and nutrient solubilization, whereas others inhibited plant growth and nodulation.…”
Section: Discussionmentioning
confidence: 99%
“…and Zn biofortification influence plant nodulation, as well as to the complex interactions among plants, microbes, and soil in biofortification processes [43]. As for the independent effect of both factors on nodulation, the inhibitory effect in the plants inoculated with T09 and T18 (both identified as T. gamsii) may be a result of the colonization dynamics in the rhizosphere, considering that nodulation success may be influenced by the timing and sequence in rhizosphere interactions between different microorganisms [59]. These results are consistent with a related study by Khan et al [60], where some Trichoderma strains enhanced plant growth and nutrient uptake by promoting root development and nutrient solubilization, whereas others inhibited plant growth and nodulation.…”
Section: Discussionmentioning
confidence: 99%
“…Since vertical transmission of gastrointestinal bacteria is not described for A. balthica , an important mechanism for colonization of the gastrointestinal tract is the “priority effect” (Walter & Ley, 2011 ). Bacterial populations establish during the early development of the symbiosis, and outcompete later arrivals (Burr et al, 2022 ). If these bacteria can colonize the gastrointestinal tract permanently, they create a local gastrointestinal microbiome that is specific to the gastrointestinal tract but shows a clear overlap with sediment and water bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial populations establish during the early development of the symbiosis, and outcompete later arrivals (Burr et al, 2022) (Suzzi et al, 2023).…”
Section: Host Identification Through Phylogenetic Marker Genesmentioning
confidence: 99%
“…A study on the legume Medicago lupulina found that inoculations with an effective Ensifer strain followed by an ineffective Ensifer strain improved plant growth, compared to the same inoculation with the order reversed [ 233 ]. Another study on the legume Medicago truncatula found that priority effects—namely plant age, inoculation order, and inoculation synchrony—strongly determined a successful colonization by either a mutualistic rhizobium or a pathogenic nematode [ 234 ]. Whether or not priority effects can negate the importance of the aforementioned factors in determining successful PGPB colonization is an open question that should receive further research.…”
Section: Intersection Of Pgpb and Ceamentioning
confidence: 99%